A Qualitative Study on Meaninglessness Formation Contexts among Nurses - Hamed Kiani-Dehkiani; SeyedAlireza Afshani; Ali Ruhani (توسعه اجتماعی)
Meaninglessness is generally argued as a major consequence of alienation, which brings concerns about how meaning is made in the social construction of bureaucratic organizations. A grounded theory method was employed to explore meaninglessness formation context among nurses in public hospitals in Yazd. Through theoretical and purposeful sampling, 20 nurses in public hospitals in the city were selected to participate in in-depth interviews. The theoretical sampling process continued until data saturation was obtained. The collected data were analyzed through open, axial and selective coding. The results yielded 16 main categories (e.g., paperwork, phobia from reporting, distorted communication between companion/patient, impression management crisis and vertical gender emotional labor, experience of emancipatory emotions, vertical system management, problematic of social relations etc.), a core category (organizing of meaninglessness among nurses), the paradigmatic model, and the theoretical schema. The findings indicated that nurses' meaninglessness mainly stemmed from the graded bureaucratic structure in the hospitals and is constantly reproduced in different domains. Nurses' resistance through action/reaction strategies ultimately leads to the normalization of meaninglessness among them.